THE USE OF DIALOGIC READING IN READING ACTIVITY BY IMPLEMENTING CHARACTER BUILDING USING LOCAL BASED LITERATURE - Puji Astuti Amalia; Arditiya Arditiya (Sebatik, 2021)
Reading is considered as one of the most important skill in learning foreign language since it is used in all language skills. However, teaching reading is quite challenging. In Permata group, young learners seem not motivated in reading activity. Pre observation showed that learners were bored during the shared reading activity. Moreover there were no interaction during the activity. Therefore, it takes teacher’s creativity and innovation to teach reading. This situation led the teacher to a new way of teaching reading, the teacher implemented a new approach in teaching reading by using dialogic reading. Moreover, the literature used by the teacher was a local based short story with the theme “Save Mahakam”. This study is a qualitative study in which the data was collected by observation and questionnaire. The study found that the dialogic reading and the short story did not only make the reading activity more interesting but they also helped the teachers to shape young learners’ characters. It found that there were some characters developed through the process of reading activity, such as 1) young learners have courage to speak, 2) young learners are friendly and sociable, 3) young learners are responsible with the environment, 4) young learners love reading, 5) young learners work in a team, 6) young learners think critically.